Characterization of Endothelial Cilia Distribution During Cerebral-Vascular Development in Zebrafish (Danio rerio). Issue 12 (December 2018) - Eisa-Beygi, Shahram; Benslimane, Fatiha M.; El-Rass, Suzan; Prabhudesai, Shubhangi; Abdelrasoul, Mahmoud Khatib Ali; Simpson, Pippa M.; Yalcin, Huseyin C.; Burrows, Patricia E.; Ramchandran, Ramani
Abstract : Objective—: Endothelial cells (ECs) sense and respond to flow-induced mechanical stress, in part, via microtubule-based projections called primary cilia. However, many critical steps during vascular morphogenesis occur independent of flow. The involvement of cilia in regulating these stages of cranial vascular morphogenesis is poorly understood because cilia have not been visualized in primary head vessels. The objective of this study was to investigate involvement of cilia in regulating the early stages of cranial vascular morphogenesis. Approach and Results—: Using high-resolution imaging of the Tg(kdrl:mCherry-CAAX ) y171 ;(bactin::Arl13b:GFP ) zebrafish line, we showed that cilia are enriched in the earliest formed cranial vessels that assemble via vasculogenesis and in angiogenic hindbrain capillaries. Cilia were more prevalent around the boundaries of putative intravascular spaces in primary and angiogenic vessels. Loss of cardiac contractility and blood flow, because of knockdown of cardiac troponin T type 2a ( tnnt2a ) expression, did not affect the distribution of cilia in primary head vasculature. In later stages of development, cilia were detected in retinal vasculature, areas of high curvature, vessel bifurcation points, and during vessel anastomosis. Loss of genes crucial for cilia biogenesis ( ift172 and ift81 ) induced intracerebral hemorrhages in an EC-autonomous manner. Exposure to high shear stress induced premature cilia disassembly in brain ECs and was associated with intracerebral hemorrhages. Conclusions—: Our study suggests a functional role for cilia in brain ECs, which is associated with the emergence and remodeling of the primary cranial vasculature. This cilia function is flow-independent, and cilia in ECs are required for cerebral-vascular stability. Abstract : Supplemental Digital Content is available in the text.